Идентификация тока источника при регулировании напряжения звена постоянного тока преобразователя частоты в системе векторного управления - Мирошник, Денис Николаевич (НТУ "ХПИ", 2013)
The researches of transvector system with the combined formation of asynchronous machine stator voltage in the traction electric drive with supply from charge battery are received in paper, providing the exclusion of current sensor at DC-link on the input of voltage source inverter. It is proposed to use channel of error indemnification at frequency converter DC link voltage control with information of asynchronous machine active power from transvector system. Maximal speed in regulation of the induction motor torque for systems with combined formation of stator voltage is achieved by active power machine channel of error indemnification in comparison with the same channel by active power of DC-link.
Keywords: автономный инвертор напряжения; импульсный преобразователь; канал компенсации статизма; активная мощность АД; контур регулирования момента